2020
DOI: 10.1021/acs.energyfuels.0c03067
|View full text |Cite
|
Sign up to set email alerts
|

Deterring Effect of Resins on the Aggregation of Asphaltenes in n-Heptane

Abstract: Asphaltene precipitation can cause clogged pipelines, of which the alleviation costs the oil industry billions of dollars per year. Asphaltenes are a diverse set of macromolecules native to crude oil and are classified by their lack of solubility in light alkanes. Resins are another native component of crude oil that have been implicated in both deterring and promoting asphaltene aggregation. Here, we design a systematic set of model asphaltenes and resins to investigate the molecular features that affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Then the solutions were homogenized by mixing with a magnetic stirrer for 30 min. Because complex components and resins (found in crude oil) can inhibit asphaltene precipitation in the micromodel [38] , [39] , the synthetic oil is utilized instead of crude oil to precipitate asphaltene.…”
Section: Methodsmentioning
confidence: 99%
“…Then the solutions were homogenized by mixing with a magnetic stirrer for 30 min. Because complex components and resins (found in crude oil) can inhibit asphaltene precipitation in the micromodel [38] , [39] , the synthetic oil is utilized instead of crude oil to precipitate asphaltene.…”
Section: Methodsmentioning
confidence: 99%
“…61 Because of their interactions with asphaltenes, resins can deter the asphaltenes aggregation process. 48 Resins can function as a bridging material that connects the polar asphaltenes to the nonpolar saturates in crude oils through various mechanisms, e.g., micelle-type formation, 37 peptization of the asphaltene core, 62 or supramolecular growth. 50 It is believed that due to the opposite surface charges of resins and asphaltenes fractions, the resins− asphaltenes molecular interactions are preferred over asphaltene−asphaltene interactions.…”
Section: Asphaltene Structurementioning
confidence: 99%
“…Polar and aromatic functional groups present within the internal molecular structure of asphaltene, including carboxylic acids, carbonyls, phenols, pyrrolic, and pyridinic nitrogen, have the capability of forming hydrogen bonds. These groups can donate or accept protons inter- and intramolecularly. , It has been found that sulfur and oxygen heteroatoms strongly contribute to the aggregation of asphaltenes particularly in n -heptane solution, and the oxygen-containing compounds possibly drive asphaltene aggregation through hydrogen bonding . The most likely mechanisms of asphaltene aggregation involve π–π interactions between aromatic sheets (electrostatic and/or van der Waals forces), hydrogen bonding between functional groups (significant in the presence of water), coordination interactions, and acid–base interactions (Figure ).…”
Section: Asphaltene Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Among all the candidates, of high interest as alternative acceptors are graphene-like small molecules capable of forming stacked structures due to π–π interactions, which enables efficient charge transfer . Asphaltenes are natural graphene-like particles, products of deep oil refining, which cost orders of magnitude less than similar synthesized carbon nanoparticles. Moreover, for the oil refining industry, the issue of asphaltene recycling and disposal is in great demand, since asphaltenes represent an abandoned byproduct. , Several studies have already demonstrated the electronic conductivity of asphaltenes, and suggested their use in various electronic applications, including the design of organic solar cells. In particular, the Chianelli group has made several attempts to create an asphaltene-based dye-sensitized solar cell, although the maximum PCE obtained did not exceed 2.0%. , Higher PCEs can be achieved through a variety of changes, from nanoscale molecular structure modifications to optimization of the device design.…”
mentioning
confidence: 99%